Qualitative water evaluation of stream Campo Alegre by influence of sewage treatment plant from the city of Santa Helena de Goiás - Rodrigues, Andriane de Melo; Silva Júnior, Édio Damásio da; Saleh, Bruno Botelho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The final disposal of sewage in aquatic environments is a fairly common practice, but which can result in risks to public health and environmental quality. This study aimed to analyze the effect of treated sewage launch on water qualityof StreamCampo Alegre in the municipality of Santa Helena de Goiás. Werecollected and analyzed the quality of samples of treated sewage and water of the streaminupstream and downstream of the release point, in two different climatic periods. Subsequently, wereevaluated the quality of treated wastewater and water of the streamunder state environmental laws. Was observed a decay of the streamwater quality for the dry period and also at the downstream point of sewagedisposal. Treated sewage attended the law as stipulated by the release into water bodies. The water quality of the stream has always been characteristic of Class 2water bodies, except for total coliforms. In general, the quality of the streamunder study was significantly altered by the launch of the treated sewage according to the presence of pathogenic microorganisms.